Changes of Geochemical Elements in Lake Sediments from Hållvastö, Sweden: An Implication for Climate Reconstruction During Transition from the Baltic Ice Lake to the Yoldia Sea Stage - Indra Sanjaya (Pusat Survei Geologi, 2015)
Three varved sediment cores from Hållvastö have been investigated to reveal shift in climate condition linked to the local event in the Baltic Sea: i.e. the transition between the Baltic Ice Lake Stage to the Yoldia Sea Stage. That local event was marked by the color change in varve clay sequences, which point to the change in varved clay forming processes. Varve diagrams were constructed for all Hållvastö sections in order to obtain a relative age based on annual varve-thickness correlations, the relative age of the cores are corresponded to 10,640 - 10,850 varve year or 11,390 - 11,610 cal yr BP. The geochemical data for this study was acquired using the Itrax, an X-Ray Fluorescence core scanner, which provides insitu high resolution, continuous, and multi element analyses. The geochemical data from the Itrax are occupied to make the elemental profiles and correlation matrices. The geochemical data are linked with lithological and loss on ignition analyses to answer the research question. It was found that the strength of associations between the studied elements (Ti, Rb, K, Zr, Si, Ca, Sr, Mn and Fe) varied over time with changes in basin status, which are ultimately driven by changes in climate. Element profiles are demonstrated several changes which could be related with the changes in hydrological and sedimentary processes. Increasing in grain size from the Baltic Ice Lake to the Yoldia Sea varve clay sequence (as indicated by Zr/Rb) could be related to the warming event during the beginning of Holocene warming event. The ice melted faster than before and increased the amount of water as sediment transport agent, thus coarser materials input to the basin increased.Keywords - Varve Clay, Baltic Sea, Baltic Ice Lake, Yoldia Sea, Paleoclimate, Itrax XRF core scanner.